An overview of after-treatment systems for diesel engines - Ayodhya, Archit Srinivasacharya; Narayanappa, Kumar Gottekere (Environmental science and pollution research international, 2018)
Vehicular pollution has become a major problem in urban areas due to the exponential rise in the number of automobiles. Typical exhaust emissions which include nitrogen oxides (NO x ), hydrocarbons (HC), carbon monoxide (CO), soot, and particulate matter (PM) undoubtedly have an unpleasant effect on the environment. Several pollution control bodies are taking this subject seriously and issuing stringent emission norms which are to be complied strictly. Thus, regulation of these harmful pollutants is the need of the hour. Alternative fuels such as biodiesels and alcohols which are considered as a potentially viable solution for the problem of fossil fuel depletion also tend to require exhaust gas after-treatment in order to comply with the upcoming emission norms. Hence, this paper attempts to give a brief insight on the development and advances of different after-treatment devices like diesel particulate filter (DPF), lean NO x trap (LNT), diesel oxidation catalyst (DOC), and selective catalytic reduction (SCR).